Influence of partial dealcoholization on the composition and sensory properties of Cabernet Sauvignon wines. (30th September 2020) - Pham, Duc-Truc; Ristic, Renata; Stockdale, Vanessa J.; Jeffery, David W.; Tuke, Jonathan; Wilkinson, Kerry
Highlights: Five wines were partially dealcoholized by reverse osmosis-evaporative perstraction. Only small changes in wine composition were observed after partial dealcoholization. Dealcoholization did not significantly affect wine aroma and flavor. The perception of some wine palate attributes were affected by ethanol removal. Attempts to identify an alcohol sweetspot were not successful. Abstract: Worldwide, winemakers are increasingly adopting alcohol management strategies to counter the higher wine ethanol concentrations observed over the past 30 years. Wines with high ethanol levels exhibit increased 'hotness' on the palate, which is generally considered to negatively impact wine quality. This study investigated changes in the chemical and sensory profiles of five Cabernet Sauvignon wines following their partial dealcoholization by reverse osmosis-evaporative perstraction (RO-EP). Descriptive analysis (DA) of wine before and after RO-EP treatment indicated dealcoholization did not strongly affect wine aroma and flavor, consistent with the small changes observed in wine chemical composition. However, significant differences in the perception of wine palate attributes were observed, with dealcoholized wines found to exhibit lower acidity, sweetness, bitterness, saltiness and/or body. Astringency was enhanced following partial dealcoholization of one wine, but diminished in another. Sensory trials were also undertaken to determine the optimal ethanol concentration of wines, or the 'alcohol sweetspot'. Two approaches to alcohol sweetspotting of dealcoholized wines were evaluated, together with two methods of statistical analysis, chi-squared goodness of fit and one proportion tests.